The Prevalence of Verocytotoxin-Producing Escherichia coli O157 (VTEC) in Dairy Cattle in Tripoli Area, Libya - Helmi H*, Gusbi A, Fares A (AlQalam Journal of Medical and Applied Sciences, 2017)
Infection with verocytotoxin-producing Escherichia coli O157 in humans can lead to mild or bloody diarrhoea with the haemolytic uremic syndrome (HUS) as possible complication. Cattle appear to be important reservoir for VTEC O157. Epidemiologic studies on the prevalence of VTEC O157 in dairy cattle in Libya have never been conducted. This information is important to develop a quantitative risk assessment model for the consumption of dairy products and meat. Hence the main objective described in this paper is to investigate the prevalence associated with VTEC O157 on dairy farms in Tripoli region. Faecal samples from 200 apparently healthy cows were collected once from 15 randomly selected dairy farms. All fecal samples were examined for VTECO157 by conventional plating using Sorbitol-MacConkey agar (SMAC). Isolated of E. coli were subjected to latex agglutination test. A structured questionnaire was used to collect information on the animals and farms. The results pointed out that, prevalence within-herd (individual) and among herds were 9% and 60% respectively. The highest prevalence of VTEC was in Janzour area (12.5%). and the lowest was in Ein Zarrah area (6.5%). Aiming at reducing risks for human by intervention at farm-level, it is of importance to reduce the number of positive animals for this, more research is needed to devise mitigation strategies that reduce farm contamination of VTEC.